Internalization of Islamic Values in Islamic Education Learning - Nurpita, Fitri; Cahyani, Mely; -, Athiyah; Tampubolon, Ayumi; Yeli, Salmaini (unprimdn.ac.id, 2025)
This article discusses the internalization of Islamic values in Islamic Religious Education (PAI) learning as a strategic effort to shape the character and personality of students who are faithful, knowledgeable, and have noble morals. The background to this study is based on the phenomenon of declining morality of the younger generation amidst globalization and technological developments, which require PAI learning to focus not only on cognitive aspects but also on the formation of Islamic attitudes and behaviors. The research method used in this article is a qualitative-descriptive method with a literature study approach (library research). Data were obtained from various relevant library sources, including books, scientific articles, previous research results, and Quranic verses and hadiths that support this research. The results of the study indicate that the internalization of Islamic values encompasses four main dimensions: faith (aqidah), worship (ibadah), morals (akhlak), and science (scientific). The process occurs through three important stages: value transformation, value transaction, and value transinternalization. Teacher strategies play a central role in the success of this process through role modeling, habituation, integration of values into learning materials, and providing advice and value reflection. Successful internalization is also influenced by a religious school environment, family support, and contextual learning media. While the negative influence of digital media and low student motivation are key challenges, internalizing Islamic values in Islamic Religious Education (PAI) requires synergistic collaboration between teachers, schools, families, and the community to create a generation that is religious, virtuous, and capable of facing the challenges of the times based on Islamic values.